(untitled) (Sciences & Technologie. C, Biotechnologies, 2016)
This work is an essay of incorporations of barley flour, at different percentages, to soft wheat flour, in order to product a cookie. It consists to a production of a witness cookie (with soft wheat flour) and mixture cookies at different percentages of barley. The incorporation of 25% of barley end up by the difficulty to mix the paste, to laminate it and to put it in tray because the paste become without cohesion. The description of fabrication led to establishment of a fabrication diagram. Tasting tests indicated that the witness cookie and the cookie with 5% of barley are almost identical and present good organoleptic characteristics. Cookies with 10%, 15% and 20% of barley present a dark color and a hard and rough crust. Chemical dosages of raw material and finished products have also been done. Nutritional Densities (ND) and Energetic Densities (ED) increased with the percentage of barley flour incorporation.